Durable flame-retardant nylon fabric and preparation method thereof

Through the combination of sulfur/nitrogen-based compounds, fatty aldehyde crosslinking agents and carboxylic acid-based catalysts, combined with plasma surface modification technology, the reaction of highly reactive hydroxymethyl groups and nylon fabrics is solved, and the flame retardant nylon fabrics are solved. The problem of insufficient effect and washing resistance performance has achieved efficient gas-phase and condensate flame retardant effects, meeting flame retardant standards and washing resistance requirements.

CN119121627APending Publication Date: 2024-12-13LANZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411286409.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The flame retardant effect and washing resistance of existing flame retardant nylon fabrics are insufficient, and traditional flame retardant has problems such as toxicity, poor thermal stability, and volatile, making it difficult to meet the fire resistance requirements of the textile industry.

Method used

Using sulfur/nitrogen-based compounds as flame retardants, combined with fatty aldehyde crosslinking agents and carboxylic acid catalysts, the reaction of highly active hydroxymethyl groups and amino groups on the surface of nylon fabrics is formed through plasma surface modification and impregnation treatment, forming a large Molecular chain flame retardant improves the bonding force between the flame retardant and the fabric, and achieves the coordinated flame retardant effect of gas phase and condensation phase.

Benefits of technology

The produced durable flame-retardant nylon fabric has an oxygen limit of 30.0 to 35.0%, reaching the flame retardant standard, and maintaining a flame retardant performance of 27.0 to 28.0% after 20 washes. It has good washing resistance and simple preparation. Craft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005043221770000101
    Figure BDA0005043221770000101
Patent Text Reader

Abstract

The invention relates to the technical field of flame retardants, and particularly discloses a durable flame-retardant nylon fabric and a preparation method thereof. Comprising the following steps: pretreating nylon fabric; carrying out plasma surface modification on the pretreated nylon fabric; dipping the surface-modified nylon fabric in a flame retardant for flame-retardant treatment, and drying and curing after dipping to obtain the durable flame-retardant nylon fabric. The flame retardant is prepared from a sulfur / nitrogen-based compound, a cross-linking agent fatty aldehyde compound, a catalyst carboxylic acid and water, amino groups of the sulfur / nitrogen-based compound react with the fatty aldehyde compound under the action of the carboxylic acid to generate high-activity hydroxymethyl, the high-activity hydroxymethyl reacts with other amino groups for the second time to form a macromolecular chain-shaped flame retardant, and in the fabric dipping process, the high-activity hydroxymethyl is subjected to secondary reaction to form the flame retardant. When the flame retardant is wound on the surface of a fabric fiber, redundant high-activity hydroxyl reacts with amino on the surface of a nylon fabric so as to be cross-linked with the fabric, so that the binding force between the flame retardant and the nylon fiber is improved, and the nylon fabric has certain washing resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardants, and in particular relates to a durable flame retardant nylon fabric and a preparation method thereof. Background Art

[0002] As a synthetic fiber, nylon has the advantages of good wear resistance, high breaking strength, and processability. It is widely used in transportation, electronic appliances, military textiles, aerospace, home decoration and other fields. However, the limiting oxygen index of nylon fabric is 20-22%, which is a flammable textile and cannot meet the fire protection regulations of the relevant textile industry. Therefore, it is of great significance to prepare durable flame-retardant nylon fabric. Flame retardants can be mainly divided into halogen flame retardants, silicon flame retardants, phosphorus flame retardants, nitrogen flame retardants, intumescent flame retardants, etc. Each single flame retardant has its own advantages and disadvantages during use. Halogen flame retardants produce toxic substances, which are not in line with the development concept of green environmental protection and have been banned. Silicon flame retardants have poor flame retardant effects and will affect the softness of fabrics. They are often mixed with phosphorus flame retardants and nitrogen flame retardants. Phosphorus flame retardants are widely used in various fabrics because of their high flame retardancy, but they have problems with poor thermal stability and high volatility. Different flame retardants are often used in combination, which is also the significance of the construction of intumescent flame retardants. At present, the research direction of flame-retardant nylon fabrics is mainly from phosphorus flame retardants to phosphorus-nitrogen and nitrogen flame retardants.

[0003] For example, Chinese patent CN103205882A discloses a method for preparing a semi-durable halogen-free flame-retardant nylon 66 fabric, wherein the fabric is first washed, dehydrated, and dried, and then impregnated with flame-retardant finishing, wherein the impregnation liquid is phosphate ester, the penetrant is isopropyl alcohol, and the flame retardant is a mixture of phosphate ester, PU glue, and butanone. The carbon loss length of the prepared nylon fabric is about 10 cm, reaching B1 level, but the flame retardant effect and water washing resistance of the nylon 66 fabric in the patent still need to be further improved. In addition, most of the current flame-retardant modified fabrics have the problem of not being resistant to water washing. Summary of the invention

[0004] The purpose of the present invention is to provide a durable flame-retardant nylon fabric and a preparation method thereof in view of the above-mentioned deficiencies in the prior art. Sulfur / nitrogen-based compounds are used as raw materials, fatty aldehydes are used as cross-linking agents, and carboxylic acids are used as catalysts. Amino groups in the sulfur / nitrogen-based compounds react with the cross-linking agent fatty aldehydes under the action of the catalyst carboxylic acids to generate highly active hydroxymethyl groups, which react with other amino groups to form a macromolecular chain flame retardant. During the process of impregnating the nylon fabric, while being entangled on the surface of the fabric fibers, the excess highly active hydroxyl groups react with the amino groups on the surface of the nylon fabric, thereby cross-linking with the fabric, which is beneficial to improving the bonding force between the flame retardant and the nylon fibers, and making the nylon fabric have certain water-washing resistance.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] The first object of the present invention is to provide a method for preparing a durable flame-retardant nylon fabric, comprising the following steps: pre-treating the nylon fabric; performing plasma surface modification on the pre-treated nylon fabric; immersing the surface-modified nylon fabric in a flame retardant for flame retardant treatment, and drying and curing the nylon fabric after immersion to obtain the durable flame-retardant nylon fabric; the flame retardant is prepared from a sulfur / nitrogen-based compound, a cross-linking agent, a catalyst and water, the sulfur / nitrogen-based compound is a compound containing both a sulfur group and an amino group, the cross-linking agent is a fatty aldehyde compound, and the catalyst is a carboxylic acid.

[0007] Furthermore, the sulfur / nitrogen-based compound is one or more of guanidine sulfamate, ammonium sulfamate, sulfamic acid, thiourea, ammonium sulfate and sulfonyl ammonium.

[0008] Furthermore, the cross-linking agent is one or more of formaldehyde, glutaraldehyde, nonanal, undecanal and lauryl aldehyde.

[0009] Furthermore, the catalyst is one or more of acetic acid, oxalic acid, citric acid, 1,2,3,4-butanetetracarboxylic acid, etc.

[0010] Furthermore, the pretreatment is to immerse the nylon fabric in a sodium hydroxide or sodium carbonate solution with a concentration of 1 to 5 wt% for 20 to 24 hours.

[0011] Furthermore, the nylon fabric is polyamide 6 or polyamide 66.

[0012] Furthermore, the surface modification is to treat the fabric surface by N2 plasma.

[0013] Furthermore, the immersion time of the flame retardant treatment is 1 to 2 hours; and / or,

[0014] The drying process is carried out at 90° C. for 2 to 4 minutes, and the curing process is carried out at 155 to 175° C. for 2 to 4 minutes.

[0015] The second object of the present invention is to provide a durable flame retardant nylon fabric prepared according to the above preparation method.

[0016] Furthermore, the mass of the flame retardant coating of the durable flame retardant nylon fabric is 17-21% of the mass of the durable flame retardant nylon fabric.

[0017] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0018] (1) The preparation of the durable flame retardant nylon fabric of the present invention is completed in three steps:

[0019] ① Fabric pretreatment: immerse the nylon fabric in sodium hydroxide or sodium carbonate aqueous solution for strong alkali treatment to achieve desizing and impurity removal on the fabric surface;

[0020] ② Surface modification: The pre-treated nylon fabric is surface modified by using N2 plasma to generate new active sites and binding sites - NH2;

[0021] ③ Flame retardant treatment: Using sulfur / nitrogen-based compounds as raw materials, fatty aldehydes as cross-linking agents, and carboxylic acids as catalysts, the amino groups in the sulfur / nitrogen-based compounds react with the cross-linking agent fatty aldehydes under the action of the catalyst carboxylic acids to generate highly active hydroxymethyl groups, which react with other amino groups to form macromolecular chain flame retardants. During the process of impregnating the fabric, while entangled on the surface of the fabric fibers, the excess highly active hydroxyl groups react with the amino groups on the surface of the nylon fabric, thereby cross-linking with the fabric, which is beneficial to improve the bonding force between the flame retardant and the nylon fiber, and make the nylon fabric have certain water-washing resistance.

[0022] (2) The flame retardant prepared by the present invention is used to impregnate nylon fabric. With the help of the sulfur group and amino group in the flame retardant, during the combustion process, the amino group decomposes under heat to produce a large amount of non-combustible gas to reduce the oxygen concentration, hinder the combustion of the fabric, and play a gas-phase flame retardant effect; the sulfur group decomposes under heat to produce sulfur dioxide, which captures active free radicals, inhibits the combustion chain reaction, and generates non-combustible gas, thereby diluting oxygen and combustible gas to exert a flame retardant effect, which mainly plays a role in the gas-phase flame retardant mechanism.

[0023] (3) The flame retardant prepared by the present invention mainly acts synergistically on nylon fabrics through condensed phase flame retardancy and gas phase flame retardancy to achieve a flame retardant effect. The limiting oxygen index of the prepared durable flame retardant nylon fabric is 30.0-35.0%, which meets the flame retardant standard. After 20 times of water washing, the limiting oxygen index is still 27.0-28.0%, which has good water washing resistance.

[0024] (4) The preparation process of the durable flame-retardant nylon fabric of the present invention is simple and can be produced on a large scale. DETAILED DESCRIPTION

[0025] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.

[0026] Example 1

[0027] Example 1 of the present application provides a method for preparing a durable flame-retardant nylon fabric, comprising the following steps:

[0028] (1) Pretreatment of nylon 6 fabric

[0029] Prepare a 4 wt % NaOH solution, soak the nylon 6 fabric in the solution for 24 hours, then rinse with deionized water for several times until the nylon 6 fabric is nearly neutral, and dry at 80° C. for later use.

[0030] (2) Preparation of flame retardant

[0031] 12.49 g of guanidine sulfamate was dissolved in deionized water and stirred until completely dissolved to obtain a flame retardant, wherein the concentration of guanidine sulfamate was 0.80 mol / L.

[0032] (3) Preparation of durable flame-retardant nylon 6 fabric

[0033] The nylon 6 fabric pretreated in step (1) is immersed in the solution of step (2) for 1 hour; the nylon 6 fabric after the immersion treatment is dried at 90°C.

[0034] Example 2

[0035] Example 2 of the present application provides a method for preparing a durable flame-retardant nylon fabric, comprising the following steps:

[0036] (1) Pretreatment of nylon 6 fabric

[0037] Prepare a 4 wt % NaOH solution, soak the nylon 6 fabric in the solution for 24 hours, then rinse with deionized water for several times until the nylon 6 fabric is nearly neutral, and dry at 80° C. for later use.

[0038] (2) Preparation of flame retardant

[0039] Dissolve 12.49 g of guanidine sulfamate in deionized water, stir until completely dissolved, add formaldehyde and acetic acid in sequence, and stir for 1 hour to fully react to obtain a flame retardant, wherein the concentration of guanidine sulfamate is 0.80 mol / L, the concentration of formaldehyde is 1.6 mol / L, and the concentration of acetic acid is 2 wt%.

[0040] (3) Preparation of durable flame-retardant nylon 6 fabric

[0041] The nylon 6 fabric pretreated in step (1) is immersed in the solution of step (2) for 1 hour; the nylon 6 fabric after the immersion treatment is dried and cured by pre-baking at 90° C. for 3 minutes and curing at 160° C. for 3 minutes.

[0042] Example 3

[0043] Example 3 of the present application provides a method for preparing a durable flame-retardant nylon fabric, comprising the following steps:

[0044] (1) Pretreatment of nylon 6 fabric

[0045] Prepare a 4 wt % NaOH solution, soak the nylon 6 fabric in the solution for 24 hours, then rinse with deionized water for several times until the nylon 6 fabric is nearly neutral, and dry at 80° C. for later use.

[0046] (2) Surface modification of nylon 6 fabric

[0047] The surface treatment of nylon 6 fabric was carried out using N2 plasma for 1 h. The nylon fabric was placed between two electrodes of dielectric barrier discharge (DBD) plasma and activated with atmospheric pressure plasma for 45 s, with a power frequency of 20,000 Hz, a power of 50 W, an output of 5 kV, and a working gas of N2 at a fixed flow rate of 3 L / min.

[0048] (3) Preparation of flame retardant

[0049] Dissolve 12.49 g of guanidine sulfamate in deionized water, stir until completely dissolved, add formaldehyde and acetic acid in sequence, and stir for 1 hour to fully react to obtain a flame retardant, wherein the concentration of guanidine sulfamate is 0.80 mol / L, the concentration of formaldehyde is 1.6 mol / L, and the concentration of acetic acid is 2 wt%.

[0050] (4) Preparation of durable flame-retardant nylon 6 fabric

[0051] The nylon 6 fabric after the surface modification treatment in step (2) is immersed in the solution of step (3) for 1 hour; the nylon 6 fabric after the immersion treatment is dried and cured, pre-baked at 90° C. for 3 minutes, and cured at 160° C. for 3 minutes.

[0052] Example 4

[0053] Example 4 of the present application provides a method for preparing a durable flame-retardant nylon fabric, comprising the following steps:

[0054] (1) Pretreatment of nylon 6 fabric

[0055] Prepare a 4 wt % NaOH solution, soak the nylon 6 fabric in the solution for 24 hours, then rinse with deionized water for several times until the nylon 6 fabric is nearly neutral, and dry at 80° C. for later use.

[0056] (2) Surface modification of nylon 6 fabric

[0057] The nylon 6 fabric was surface treated with N2 plasma for 1 h.

[0058] (3) Preparation of flame retardant

[0059] Dissolve 12.30 g of thiourea in deionized water, stir until completely dissolved, then add formaldehyde and acetic acid in sequence, and stir for 1 hour until fully reacted to obtain a flame retardant, wherein the concentration of thiourea is 1.6 mol / L, the concentration of formaldehyde is 3.2 mol / L, and the concentration of acetic acid is 4 wt%.

[0060] (4) Preparation of durable flame-retardant nylon 6 fabric

[0061] The nylon 6 fabric after the surface modification treatment in step (2) is immersed in the solution of step (3) for 1 hour; the nylon 6 fabric after the immersion treatment is dried and cured, pre-baked at 90° C. for 3 minutes, and cured at 160° C. for 3 minutes.

[0062] Example 5

[0063] Example 5 of the present application provides a method for preparing a durable flame-retardant nylon fabric, comprising the following steps:

[0064] (1) Pretreatment of nylon 66 fabric

[0065] Prepare a 4 wt % NaOH solution, soak the nylon 66 fabric in the solution for 24 hours, then rinse with deionized water for several times until the nylon 66 fabric is nearly neutral, and dry at 80° C. for later use.

[0066] (2) Surface modification of nylon 66 fabric

[0067] The surface treatment of nylon 66 fabric was carried out using N2 plasma for 1 h. The nylon fabric was placed between two electrodes of dielectric barrier discharge (DBD) plasma and activated with atmospheric pressure plasma for 45 s, with a power frequency of 20,000 Hz, a power of 50 W, an output of 5 kV, and a working gas of N2 at a fixed flow rate of 3 L / min.

[0068] (3) Preparation of flame retardant

[0069] Dissolve 12.30 g of thiourea in deionized water, stir until completely dissolved, then add glutaraldehyde and acetic acid in sequence, and stir for 1 hour until fully reacted to obtain a flame retardant, wherein the concentration of thiourea is 1.6 mol / L, the concentration of glutaraldehyde is 1.6 mol / L, and the concentration of acetic acid is 4 wt%.

[0070] (4) Preparation of durable flame-retardant nylon 66 fabric

[0071] The nylon 66 fabric after the surface modification treatment in step (2) is immersed in the solution of step (3) for 1 hour; the nylon 66 fabric after the immersion treatment is dried and cured, pre-baked at 90° C. for 3 minutes, and cured at 160° C. for 3 minutes.

[0072] Example 6

[0073] Example 6 of the present application provides a method for preparing a durable flame-retardant nylon fabric, comprising the following steps:

[0074] (1) Pretreatment of nylon 66 fabric

[0075] Prepare a 4 wt % NaOH solution, soak the nylon 66 fabric in the solution for 24 hours, then rinse with deionized water for several times until the nylon 66 fabric is nearly neutral, and dry at 80° C. for later use.

[0076] (2) Surface modification of nylon 66 fabric

[0077] The surface treatment of nylon 66 fabric was carried out using N2 plasma for 1 h. The nylon fabric was placed between two electrodes of dielectric barrier discharge (DBD) plasma and activated with atmospheric pressure plasma for 45 s, with a power frequency of 20,000 Hz, a power of 50 W, an output of 5 kV, and a working gas of N2 at a fixed flow rate of 3 L / min.

[0078] (3) Preparation of flame retardant

[0079] Dissolve 12.49 g of guanidine sulfamate in deionized water, stir until completely dissolved, add glutaraldehyde and acetic acid in sequence, and stir for 1 hour to fully react to obtain a flame retardant, wherein the concentration of guanidine sulfamate is 0.8 mol / L, the concentration of glutaraldehyde is 0.8 mol / L, and the concentration of acetic acid is 2 wt%.

[0080] (4) Preparation of durable flame-retardant nylon 66 fabric

[0081] The nylon 66 fabric after the surface modification treatment in step (2) is immersed in the solution of step (3) for 1 hour; the nylon 66 fabric after the immersion treatment is dried and cured, pre-baked at 90° C. for 3 minutes, and cured at 160° C. for 3 minutes.

[0082] The mass of the flame retardant coating of the durable flame retardant nylon fabric prepared in Examples 1 to 6 is 17 to 21% of the mass of the durable flame retardant nylon fabric. The flame retardant nylon fabric prepared in Examples 1 to 6 of the present application was tested for limiting oxygen index (LOI:%), water washing resistance and droplet performance, and the results are shown in Table 1. The test conditions are as follows:

[0083] Limiting oxygen index test: According to GB / T5454 1997 "Oxygen Index Method for Determination of Combustion Performance of Textiles", the test method is to place the sample under vertical test conditions and test the minimum oxygen concentration (also called limiting oxygen index) that just maintains combustion in an oxygen and nitrogen mixed flow. The sample is clamped on a sample clamp and placed vertically in a combustion tube. In the upward oxygen flow, the upper end of the sample is ignited, its combustion characteristics are observed, and its afterburning time (no more than 2 minutes) or destruction length (no more than 40mm) is compared with the specified limit value. By testing a series of samples in different oxygen concentrations, the minimum oxygen concentration value expressed as the percentage of oxygen to maintain combustion can be measured.

[0084] Washability test: Use a magnetic stirrer and a beaker to complete the washability test. Add 500ml of tap water into a 500ml beaker, and place the prepared flame-retardant nylon fabric in the beaker for stirring and washing. Set the speed of the magnetic stirrer to 600r / min, and 10min is one wash.

[0085] Vertical burning test: GB / T 5455-2014 "Determination of vertical burning length, smoldering and afterflaming time of textiles".

[0086] Droplet performance test: Use the vertical burning method to ignite the nylon fabric with a 4cm long flame for 3 seconds. After removing the flame until the burning is completed, observe whether there are droplets falling, and express the results in words.

[0087] According to the test results in Table 1 below, it can be seen that Example 1 only adds the main flame retardant components in the flame retardant system separately, while Example 2 adds the cross-linking agent and the catalyst at the same time. Compared with Example 1, the LOI of Example 2 is lower, indicating that the addition of the cross-linking agent and the catalyst affects the structure of the flame retardant, resulting in a decrease in its flame retardant ability. However, after 20LCs, the LOI is improved compared with that of Example 1, indicating that the introduction of the cross-linking agent and the catalyst can improve the water washing resistance of the fabric; this is because the amino group in the sulfur / nitrogen compound reacts with the aldehyde group in the cross-linking agent under the action of the catalyst to generate highly active hydroxymethyl, which further reacts with other amino groups to generate macromolecular chains, and can also cross-link with the amino group on the nylon fabric during the process of impregnating the fabric, thereby improving the bonding force between the fabric and the flame retardant. However, the surface of the nylon fabric is highly hydrophobic, with fewer active functional groups and only a small amount of less active secondary amine groups, so that the cross-linking effect with the highly active hydroxymethyl in the flame retardant is not obvious, so that after 20LCs, the LOI of the fabric is only maintained at 24.1%. Although it has certain water washing resistance, it does not meet the flame retardant requirements. Examples 3 to 6 are surface plasma modified on the basis of Example 2. Compared with Example 2, it can be seen that the surface modification can further improve the water washability of the nylon fabric, so that it still has good flame retardant properties after 20LCs. This is attributed to the fact that after the fabric is surface modified by N2 plasma, new active sites and binding sites -NH2 are generated on the surface, so that in the subsequent flame retardant treatment process, certain highly active functional groups can react with the highly active hydroxymethyl in the flame retardant, thereby further improving the bonding force between the flame retardant and the nylon fabric.

[0088] Table 1. Flame retardant properties and water washability results.

[0089]

[0090] The LOI of the flame-retardant nylon fabrics prepared in Examples 3 to 6 is much higher than that before impregnation after impregnation, and all meet the flame retardant standard (flammable: LOI <20%; combustible: LOI between 20% and 26%; flame retardant: LOI between 27% and 35%; non-flammable: LOI>35%), and the vertical combustion reaches Class B1 (Class B1: damaged length ≤150mm, afterflaming time ≤5s, smoldering time ≤5s; Class B2: damaged length ≤200mm, afterflaming time ≤15s, smoldering time ≤15s), which shows that the flame-retardant fabrics prepared in Examples 3 to 6 of the present application have excellent flame retardant properties; after 20 times of washing, the LOI value is still between 27% and 35%, reaching the flame retardant standard, and the vertical combustion still meets Class B1, with excellent water washing resistance, no droplet phenomenon, and a significant improvement compared with before impregnation.

[0091] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a durable flame retardant nylon fabric, It is characterized in that The following steps are involved: Pre-treating nylon fabrics; performing plasma surface modification on the pretreated nylon fabric; The surface-modified nylon fabric is immersed in a flame retardant for flame retardant treatment, and after the immersion, it is dried and solidified to obtain a durable flame retardant nylon fabric; the flame retardant is prepared from a sulfur / nitrogen-based compound, a cross-linking agent, a catalyst and water, the sulfur / nitrogen-based compound is a compound containing both a sulfur group and an amino group, the cross-linking agent is a fatty aldehyde compound, and the catalyst is a carboxylic acid.

2. The preparation method according to claim 1, It is characterized in that The sulfur / nitrogen-based compound is one or more of guanidine sulfamate, ammonium sulfamate, sulfamic acid, thiourea, ammonium sulfate and sulfonyl ammonium.

3. The preparation method according to claim 1, It is characterized in that The cross-linking agent is one or more of formaldehyde, glutaraldehyde, nonanal, undecanal and lauryl aldehyde.

4. The preparation method according to claim 3, It is characterized in that The catalyst is one or more of acetic acid, oxalic acid, citric acid, 1,2,3,4-butanetetracarboxylic acid, etc.

5. The preparation method according to claim 1, It is characterized in that The pretreatment is to immerse the nylon fabric in a sodium hydroxide or sodium carbonate solution with a concentration of 1 to 5 wt% for 20 to 24 hours.

6. The preparation method according to claim 1, It is characterized in that The nylon fabric is polyamide 6 or polyamide 66.

7. The preparation method according to claim 1, It is characterized in that The surface modification is carried out by N 2 Plasma treatment of the fabric surface.

8. The preparation method according to claim 1, It is characterized in that The immersion time of the flame retardant treatment is 1 to 2 hours; and / or, The drying process is carried out at 90° C. for 2 to 4 minutes, and the curing process is carried out at 155 to 175° C. for 2 to 4 minutes.

9. A durable flame-retardant nylon fabric prepared by the preparation method according to any one of claims 1 to 8.

10. The durable flame retardant nylon fabric according to claim 9, It is characterized in that The mass of the flame retardant coating of the durable flame retardant nylon fabric is 17-21% of the mass of the durable flame retardant nylon fabric.

Citation Information

Patent Citations

  • Manufacture method of semi-durable halogen-free flame-retardant nylon 66 fabric

    CN103205882A